THE IMPACT OF TOURISM INDUSTRY ON LOCAL ECONOMY: CASE OF MALAYSIA - Noor Sharida,; Azreen Shaliza,; Wan Nur Syafiqah, (Journal of Islamic, Social, Economics and Development, 2023)
The purpose of this study is to study the impact of tourism industry on Malaysia economy using time series data of 30 years from 1991 until 2021. Additionally, four independent variables: tourism receipt, tourism expenditure, capital investment and exchange rate have been chosen. Using DOLS framework, tests like correlation, unit root test and cointegration test are conducted to get meaningful results. Tourism receipt, tourism expenditure, capital investment and exchange rate as independent variable have significant relationship on Malaysia economic growth. Moreover, the most significant independent variable is exchange rate, followed by tourism expenditure, capital investment and tourism receipts. The findings also show that tourism receipts, tourism expenditure, capital investment and exchange rate have long-run relationship and significantly affecting the economic growth.